Addressing the road trauma burden in China: Exploring attitudes, behaviours, risk perceptions and cultural uniqueness. (October 2016) - Fleiter, Judy J.; Watson, Barry
Highlights: 239 suspended drivers undergoing retraining were surveyed in China. Perceptions of safe driving speeds revealed differences compared to preferred speeds. Perceptions of dangerous on-road behaviours were reported. Drink driving and speeding were perceived as most dangerous. Culturally-specific issues (face saving and social influence) must be considered. Abstract: As China continues to motorise rapidly, solutions are needed to reduce the burden of road trauma that is spread inequitably across the community. Little is currently known about how new drivers are trained to deal with on-road challenges, and little is also known about the perceptions, behaviours and attitudes of road users in China. This paper reports on a pilot study conducted in a driver retraining facility in one Chinese city where people who have had their licence suspended for accrual of 12 demerit points in a one year period must attend compulsory retraining in order to regain their licence. A sample of 239 suspended drivers responded to an anonymous questionnaire that sought information about preferred driving speeds and perceptions of safe driving speeds across two speed zones. Responses indicated that speeds higher than the posted limits were commonly reported, and that there was incongruence between preferred and safe speeds, such that a greater proportion of drivers reported preferred speeds that were substantially faster than what were reported as safe speeds. Participants with more driving experience reported significantly fewer crashes than newly licensed drivers (less than 2 years licensed) but no differences were found in offences when compared across groups with different levels of driving experience. Perceptions of risky behaviours were assessed by asking participants to describe what they considered to be the most dangerous on-road behaviours. Speeding and drink driving were the most commonly reported by far, followed by issues such as fatigue, ignoring traffic rules, not obeying traffic rules, phone use while driving, and non-use of seatbelts, which attracted an extremely low response which seems consistent with previously reported low belt wearing rates, unfavourable attitudes towards seatbelt use, and low levels of enforcement. Finally, observations about culturally specific considerations are made from previous research conducted by the authors and others. Specifically, issues of saving face and the importance and pervasiveness of social networks and social influence are discussed with particular regard to how any future countermeasures need to be informed by a thorough understanding of Chinese customs and culture.